Identification of MRC2 and CD209 receptors as targets for photodynamic therapy of retinoblastoma using mesoporous silica nanoparticles1. Issue 92 (8th October 2015) - Gallud, A.; Warther, D.; Maynadier, M.; Sefta, M.; Poyer, F.; Thomas, C. D.; Rouxel, C.; Mongin, O.; Blanchard-Desce, M.; Morère, A.; Raehm, L.; Maillard, P.; et al.
<x xml:space="preserve">Abstract</x> An overexpression of MRC2 and CD209 mannose receptors was revealed in retinoblastoma and antibodies against these receptors were grafted to multifunctional nanoparticles for targeting of imaging and photodynamic therapy.